Validity of the session rating of perceived exertion for monitoring exercise demands in youth soccer players - Rodriguez-Marroyo, J. A.; Antoñan, C. (International Journal of Sports Physiology and Performance, 2015)
Purpose: The purpose of this study was to examine the concurrent and construct validity of the Borg (0-10) and children`s OMNI scales for quantifying the exercise intensity and training load (TL) in youth soccer players. Methods: Twelve children (mean ± SD age 11.4 ± 0.5 y, height 154.3 ± 6.5 cm, body mass 39.5 ± 5.4 kg) took part in this study. Exercise intensity and TL were calculated on the basis of the session rating of perceived exertion (sRPE) and heart rate (HR; Edwards method) during 20 technical-tactical training sessions. Players` sRPEs were obtained from the Borg and OMNI scales. Results: Low correlations between HR-based TL and sRPE TL based on the Borg (r = .17, P = .335) and OMNI (r = .34, P = .007) scales were obtained. Significant (P < .001) relationships in sRPE (r = .76) and TL (r = .79) between RPE scales were found. Conclusion: The current data do not support the relationship between the sRPE and HR methods for quantifying TL in youth soccer players. However, the sRPE method could be considered a better indicator of global internal TL, since sRPE is a measure of both physical and psychological stress. In addition, the authors demonstrated the construct validity for the OMNI scale to control exercise demands.